2017
DOI: 10.14419/ijet.v6i4.8326
|View full text |Cite
|
Sign up to set email alerts
|

PAPR reduction for FBMC/OQAM using hybrid scheme of different Precoding transform and mu-law companding

Abstract: The filter banks multicarrier with offset quadrature amplitude modulation (FBMC/OQAM) is developing multicarrier modulation technique used in the next wireless communication system (5G). FBMC/OQAM supports high data rate and high band width efficiency. However, one of the major drawbacks of FBMC system is high peak to Average Power Ratio (PAPR) of the transmitted signal, which causes serious degradation in performance of the system. Therefore, it is required to use a proper PAPR scheme at the transmitter to re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
8
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 11 publications
0
8
0
Order By: Relevance
“…The authors in [ 30 ] showed that DST- is better than the WHT- , DHT- , and DCT- from the PAPR reduction point of view. The model in [ 30 ] considered only the AWGN channel and neglected HPA. The authors in [ 31 ] introduced DST-A without any comparison with the previous precoding-companding techniques.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…The authors in [ 30 ] showed that DST- is better than the WHT- , DHT- , and DCT- from the PAPR reduction point of view. The model in [ 30 ] considered only the AWGN channel and neglected HPA. The authors in [ 31 ] introduced DST-A without any comparison with the previous precoding-companding techniques.…”
Section: Introductionmentioning
confidence: 99%
“…The limitations of the discussed works are summarized as follows: The authors in [ 22 , 24 , 27 , 28 , 30 , 32 , 33 , 34 , 36 , 37 ] hybridized -law with different precoding matrices due to its high PAPR reduction gain. However, BER and OOB radiation are more important metrics than PAPR reduction gain when working with PAPR reduction techniques that cause BER degradation, such as companding techniques.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations